Genital abnormalities in two cow heifers born as dizygotic heterosexual twins - SOOD, PANKAJ; SINGH, MADHUMEET; VASISHTA, N K (The Indian Journal of Animal Reproduction, 2023)
Genital abnormalities in two heifers born as coturn has been reported in the present paper.